1997
DOI: 10.1016/s0092-8674(00)80521-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation of p53 Sequence-Specific DNA Binding by Acetylation of the p53 C-Terminal Domain

Abstract: The tumor suppressor p53 exerts antiproliferation effects through its ability to function as a sequence-specific DNA-binding transcription factor. Here, we demonstrate that p53 can be modified by acetylation both in vivo and in vitro. Remarkably, the site of p53 that is acetylated by its coactivator, p300, resides in a C-terminal domain known to be critical for the regulation of p53 DNA binding. Furthermore, the acetylation of p53 can dramatically stimulate its sequence-specific DNA-binding activity, possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

64
2,010
5
18

Year Published

1998
1998
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 2,351 publications
(2,097 citation statements)
references
References 76 publications
64
2,010
5
18
Order By: Relevance
“…These recent ®ndings suggest that activation of sequence-speci®c DNAbinding by p53 in response to DNA damage may be mediated through CBP/p300 and/or PCAF. Gu and Roeder showed that p300 acetylates the carboxyl terminus of p53 (Gu and Roeder, 1997). Recently Sakaguchi et al showed that PCAF acetylated p53 in vitro on Lys 320 .…”
Section: Regulation Of P53 Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…These recent ®ndings suggest that activation of sequence-speci®c DNAbinding by p53 in response to DNA damage may be mediated through CBP/p300 and/or PCAF. Gu and Roeder showed that p300 acetylates the carboxyl terminus of p53 (Gu and Roeder, 1997). Recently Sakaguchi et al showed that PCAF acetylated p53 in vitro on Lys 320 .…”
Section: Regulation Of P53 Functionmentioning
confidence: 99%
“…p53 binds strongly to strand breaks by its C-terminal domain (Nelson and and this leads to the stabilization and activation of the protein. Several processes might be implicated in activating p53, including phosphorylation, glycosylation, binding to regulatory proteins, alternative splicing and acetylation (Gu and Roeder, 1997;Siliciano et al, 1997;Giaccia and Kastan, 1998). Perhaps the best studied activator of p53 is DNA damage following ionizing irradiation.…”
Section: Amino-terminal Region Of P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the DNA binding and transcriptional activity of p53 protein increased signi®cantly during di erentiation (Figure 3). The increase in stability and activity of p53 appears to occur simultaneously, and therefore may result from a single change such as phosphorylation or acetylation of the protein Lane, 1994, 1995;Gu and Roeder, 1997). Changes in p53 stability and activity in response to di erent physiological conditions were previously demonstrated.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study has shown that enhanced phosphorylation of p53 in cells treated with okadaic acid was correlated with an enhanced transcriptional activity of the protein (Lohrum and Scheidtmann, 1996). p53 protein can also be acetylated on its carboxyl-terminal domain (Gu and Roeder, 1997). Acetylation of p53 can dramatically stimulate its sequence-speci®c DNA-binding activity.…”
Section: Discussionmentioning
confidence: 99%